How Do Agents React to Dynamic Wage Increases? An Experimental Study - Dirk Sliwka; Peter Werner (Institute for the Study of Labor (IZA), 2016)
We investigate how workers' performance is affected by the timing of wages in a real-effort experiment. In all treatments agents earn the same wage sum but wage increases are distributed differently over time. We find that agents work harder under increasing wage profiles if they do not know these profiles in advance. A profile that continuously increases wages by small amounts raises performance by about 15% relative to a constant wage. The effort reactions can be organized by a model in which agents reciprocally respond to wage impulses, comparing wages to an adaptive reference standard determined by the previous wage.
Keywords: M12; C91; 330; wage; reciprocity; reference point